Socio demographic profiles of Rheumatic Heart Disease (RHD) patients In Sabah - Narwani Hussin; Wong, Mabelle; Liew, Houng Bang; Liau, Siow Yen (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2016)
Introduction Rheumatic Heart Disease (RHD) has been thought as a disease of poor socioeconomic status. It is more prevalent in underdeveloped and developing countries than in developed countries. It is also common among the population with multiple social issues such as overcrowded dwellings, undernutrition, poor sanitation and suboptimal medical care. This study was done to review the socio demographic profiles of RHD patients in Hospital Queen Elizabeth (HQE) ll, Kota Kinabalu, Sabah. Methods A secondary data review of all patients registered under the RHD registry in HQE ll for one- year starting from July 2013 to June 2014. Results 204 RHD patients were included. Nearly three quarter (74.0%) were female. The mean age was 40.43 (14.75) years old. 61.1% has completed secondary education. 42.7% were housewives. The mean monthly income was RM 1363.83 (1297.05) which was categorized under the vulnerable income group. When they were categorized under the poverty level and the vulnerable income group, 42.6% and 76.5% of them fell under those categories respectively. The nearest health facilities to their houses were district hospitals (33.3%) with the mean distance of 9.17 km and health clinics (30.8%) with the mean distance of 4.27 km. Only 11.5% of them lived near the specialist hospitals with the mean distance of 21.32 km. Conclusions Results from this review suggested that majority of RHD patients were in the low socioeconomic group with less access to health care facilities with specialist care. They are the most vulnerable groups and need to be prioritized in the specialized care program.